Mirror image polydactyly in a foot of young female with late presentation: management and three years follow-up - Mohammed Yousof Bakhiet; WalyeldinElnour Mohamed Elfakey; Mohamed Daffalla Awadalla Gismalla (Elsevier, 2023)
Background: Polydactyly (extra digits) is a common congenital anomaly which has familial tendency and its incidence vary widely a according to many factors including race, geographical distribution and familial tendency. It's commonly affect the hands but also can be found in the foot. We report a case of mirror foot polydactyly with late presentation with successful management. Case presentation: A 17-year-old female patient presented to our plastic surgery clinic complain of left foot deformity and inability to wear her shoe (closed) since birth. Examination of the left foot showed 4 extra digits in the medial aspect. The diagnosis of polydactyly (mirror foot) was made based on clinical and radiological finding. She underwent excision of the extra digit with correct the valgus deformity of the big toe. She had no postoperative complications with excellent result after 6 years follow up. Conclusion: This a case of mirror foot (9 toes) with late presentation. We successfully treated this case by removing the extra digit and correction of varus deformity of the big toe. Despite the late presentation, the outcome is good